Hitchcock on Hitchcock : selected writings and interviews. - Hitchcock, Alfred, 1899-1980 (University of California Press, 2014)
This second volume of Alfred Hitchcock's reflections on his life and work and the art of cinema contains material long out of print, not easily accessible, and in some cases forgotten or unknown. Edited by Sidney Gottlieb, this new collection of interviews, articles with the great director's byline, and ""as-told-to"" pieces provides an enlivening perspective on a career that spanned seven decades and transformed the history of cinema. In writings and interviews imbued with the same exuberance and originality that he brought to his films, Hitchcock ranges from accounts of his own life and exper